KOMPOSISI DAN STRUKTUR VEGETASI STRATA POHON DI KAWASAN WISATA HAPANASAN DESA SIALANG JAYA-PASIR PENGARAIAN SEBAGAI ALTERNATIF PENGEMBANGAN HANDOUT PADA KONSEP KEANEKARAGAMAN HAYATI DI SMA - Khairunnisa '; Nursal '; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was to determine the composition and structure of vegetation strata tree in Tourism Regions Hapanasan Sialang Jaya village of Pasir Pengaraian and develop a handout to the concept of biodiversity in the senior high school. The study was conducted in November 2013 and June 2014. The study was carried out by two phases: biological research on the composition and structure of vegetation and tree strata, development stage handout. This study used a survey method. Mechanical conducting a survey conducted using the method with plot size 20x20m plots distributed on a line (transect). Sample was done by using purposive sampling. The study was conducted in zone A is the zone that should not be disturbed and there are two stations were selected as the study site. The results showed that the composition of the vegetation strata tree on two research stations in Area Tourism Hapanasan found 37 species of trees from 19 tribes. The highest importance value index spesies was Mahang 2 (Macaranga hypoleuca) with a value of 101.011% and the lowest spesies was Kiara Payung (Filicium decipiens) with a value of 2.696%. Diversity index (H') in station I was high (3.255) and at station II was medium (2.168). The results of the research have been developed as a handout that is the material of Biodiversity in high school class X.Key Words: species composition, vegetation structure, handout